A pilot study of vidofludimus calcium for treatment of primary sclerosing cholangitis. Issue 7 (3rd March 2022) - Carey, Elizabeth J.; Eaton, John; Clayton, Mitchell; Gossard, Andrea; Iqbal, Sara; Ullah, Hamid; Zhang, Nan; Butterfield, Richard; Lindor, Keith D.
Abstract: The purpose of this pilot study was to explore the efficacy, safety, and tolerability of vidofludimus calcium (VC) in the treatment of primary sclerosing cholangitis (PSC). This was a single‐arm open‐label pilot study with a cohort of 18 patients with PSC. Study patients received VC for a period of 6 months. The study was undertaken at two sites, Mayo Clinic, Rochester, MN, and Mayo Clinic, Phoenix, AZ. The primary endpoint of the study was improvement of serum alkaline phosphatase (ALP) at the end of the study. Secondary endpoints included assessment of other liver biomarkers (bilirubin, alanine aminotransferase, and aspartate aminotransferase). Of 18 patients enrolled, 11 completed the 6 months of study treatment. Patients who completed treatment versus those who did not were similar other than a significantly higher direct bilirubin at baseline in the group that completed treatment (mean ± SD, 0.4 ± 0.3 versus 0.1 ± 0.1, p = 0.04). By intent to treat analysis, the primary outcome was met in 16.7% (3/18) of patients. By per‐protocol analysis, including only patients who completed treatment, normalization of ALP occurred in 27.7% (3/11) at week 24 (95% confidence interval, 6.0% to 61.0%). VC was well tolerated with no drug‐related serious adverse events. Conclusion: This proof of concept study provides support for further exploration of VC in patients with PSC. Abstract : This open‐label pilot trial of Vidofludimus calcium, a novel DHODH inhibitor, shows reduction in alkaline phosphatase in a significant number of patients. Vidofludimus calcium deserves further study with larger, randomized, controlled trials in this disease.image